![5sin^2x+3sinx*cosx-3cos^2x-2(cos^2x+sin^2x)=0;\\3sin^2x+3sinx*cosx-5cos^2x=0;\\\left[\begin{array}{ccc}\left \{ {{cos^2x=0} \atop {3sin^2x+3sinx*0-5*0=0}} \right. \\\left \{ {{cos^2x\neq 0} \atop {cos^2x(3tg^2x+3tgx-5)=0}} \right. \\\end{array} 5sin^2x+3sinx*cosx-3cos^2x-2(cos^2x+sin^2x)=0;\\3sin^2x+3sinx*cosx-5cos^2x=0;\\\left[\begin{array}{ccc}\left \{ {{cos^2x=0} \atop {3sin^2x+3sinx*0-5*0=0}} \right. \\\left \{ {{cos^2x\neq 0} \atop {cos^2x(3tg^2x+3tgx-5)=0}} \right. \\\end{array}](https://tex.z-dn.net/?f=5sin%5E2x%2B3sinx%2Acosx-3cos%5E2x-2%28cos%5E2x%2Bsin%5E2x%29%3D0%3B%5C%5C3sin%5E2x%2B3sinx%2Acosx-5cos%5E2x%3D0%3B%5C%5C%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D%5Cleft%20%5C%7B%20%7B%7Bcos%5E2x%3D0%7D%20%5Catop%20%7B3sin%5E2x%2B3sinx%2A0-5%2A0%3D0%7D%7D%20%5Cright.%20%5C%5C%5Cleft%20%5C%7B%20%7B%7Bcos%5E2x%5Cneq%200%7D%20%5Catop%20%7Bcos%5E2x%283tg%5E2x%2B3tgx-5%29%3D0%7D%7D%20%5Cright.%20%5C%5C%5Cend%7Barray%7D)
net+resheniiy\right. \\\left \{ {{cos^2x\neq 0} \atop {3tg^2x+3tgx-5=0}} \right. \\\end{array}" alt="\left[\begin{array}{ccc}\left \{ {{cos^2x=0} \atop {sin^2x=0}}; cos^2x+sin^2x\neq 0=>net+resheniiy\right. \\\left \{ {{cos^2x\neq 0} \atop {3tg^2x+3tgx-5=0}} \right. \\\end{array}" align="absmiddle" class="latex-formula">
tgx=a; D=9+20*3=69
![\left \{ {{cosx\neq 0} \atop {tgx=\frac{-3б\sqrt{69} }{6} } \right. \left \{ {{cosx\neq 0} \atop {tgx=\frac{-3б\sqrt{69} }{6} } \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Bcosx%5Cneq%200%7D%20%5Catop%20%7Btgx%3D%5Cfrac%7B-3%D0%B1%5Csqrt%7B69%7D%20%7D%7B6%7D%20%7D%20%5Cright.)
Ответ: x={arctg((-3±√69)/6)+pi*n}, n∈Z.